Congridae - Bañon, Rafael; Arronte, Juan Carlos; Rodriguez-Cabello, Cristina; Piñeiro, Carmen-Gloria; Punzon, Antonio; Serrano, Alberto (Zenodo, 2016)
Family Congridae Conger conger (Linnaeus, 1758)—European conger 208 specimens were caught at depths between 643 and 914 m. Length data were available for 37 specimens ranging from 36 to 141 cm TL (73.8±33.3). Habitat and Distribution: benthic species living in rocky and sandy bottoms between 10 and 1,171 m. Northeast Atlantic, from Norway and Iceland to Senegal, the Mediterranean, and the western Black Seas. Vulnerability: DD (IUCN), VHV (FishBase). Pseudophichthys splendens (Lea, 1913) —Purplemouthed conger 3 specimens, 1 adult of 31 cm TL and 2 juveniles of 12 and 15 cm TL, were recorded at depths between 887 and 1,041 m. Habitat and Distribution: bathydemersal species of amphi-Atlantic distribution, between 37 and 1,647 m depth. Off the western Atlantic Ocean, from Canada (larval specimens) to Brazil, while off the eastern Atlantic Ocean from Morocco, the Canary and Azores islands, and the Gulf of Guinea. These records constitute a northward range extension of their known distribution in the eastern Atlantic (Bañón et al. 2011). Vulnerability: DD (IUCN), LMV (FishBase). Published as part of Bañon, Rafael, Arronte, Juan Carlos, Rodriguez-Cabello, Cristina, Piñeiro, Carmen-Gloria, Punzon, Antonio & Serrano, Alberto, 2016, Commented checklist of marine fishes from the Galicia Bank seamount (NW Spain), pp. 293-333 in Zootaxa 4067 (3) on page 304, DOI:10.11646/zootaxa.4067.3.2, http://zenodo.org/record/256670